Konstruksi Sosial Kritis dalam Pemberitaan Tirto.id terhadap Reaksi Publik pada Kasus Pelarangan Pengecer Jual LPG 3 Kg - Syaifuddin Muhammad Mirza; Hendra Alfani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the critical social construction developed by the online media Tirto.id in its coverage of the government policy banning retailers from selling 3 Kg LPG cylinders, issued by the Minister of Energy and Mineral Resources in February 2025. The policy sparked broad public reaction due to its sudden implementation, lack of proper dissemination, and failure to consider the geographical and economic access of marginalized communities. In this context, media functions as a reality-construction agent that frames issues through particular perspectives. Using Robert N. Entman’s framing analysis model, this study explores how Tirto.id defines the problem, diagnoses the causes, makes moral judgments, and offers remedies regarding the issue. The findings show that Tirto.id consistently aligns with marginalized groups, presenting narratives, citizen testimonials, and expert critiques against the policy. The dominant framing emphasizes government failure to anticipate social impacts and highlights a lack of coordination among state agencies. Therefore, Tirto.id acts not only as an information channel but also as a public opinion shaper, advocating for social justice through its editorial stance. This study underscores the importance of media literacy and the role of critical journalism in holding public policies accountable.